A New Approach for East Natuna Gas Utilization - Fiqi Giffari; Paramita Widiastuti; Lisna Rosmayati; Nofrizal Nofrizal; Dadan Kusdiana (Scientific Contributions Oil and Gas, 2021)
The Natuna Gas Field has a potential gas reserve of 222 TCF, but this gas field has a very high CO, content of up to 71%. The high composition of CO, content and its location, which is too far from the market, causes the best option to use the Natuna's gas by converting it to liquid. Dimethyl Ether (DME) is a choice of liquid products that have a good potential as alternative energy for household LPG. A more in-depth study of the options for using the Natuna's gas into DME product via direct process was carried out in this study. The methodology used is initiated by determining the type of facilities needed and then conducting a process simulation to determine the mass balance, energy balance, and design of the equipment used. Process simulation and economic simulation show that the Natuna Gas Field is technically feasible to be developed into a DME product with a capacity of 1,800 MMSCFD, resulting in 21,245 MT/day DME. Upstream and downstream integration economic scheme produces a better economic result (ROI: 6.34%) compared to an upstream economic scheme (ROI: 0.63%). Apart from that, tax incentives on the downstream scheme can increase the project economy, and the scenario of tax holiday is the most beneficial for developers and the government.